Congestive Heart Failure Cardiopoietic Regenerative Therapy (CHART‐1) trial design. (14th December 2015) - Bartunek, Jozef; Davison, Beth; Sherman, Warren; Povsic, Thomas; Henry, Timothy D.; Gersh, Bernard; Metra, Marco; Filippatos, Gerasimos; Hajjar, Roger; Behfar, Atta; Homsy, Christian; Cotter, Gad; et al.
Abstract: Aims: Cardiopoiesis is a conditioning programme that aims to upgrade the cardioregenerative aptitude of patient‐derived stem cells through lineage specification. Cardiopoietic stem cells tested initially for feasibility and safety exhibited signs of clinical benefit in patients with ischaemic heart failure (HF) warranting definitive evaluation. Accordingly, CHART‐1 is designed as a large randomized, sham‐controlled multicentre study aimed to validate cardiopoietic stem cell therapy. Methods: Patients ( n = 240) with chronic HF secondary to ischaemic heart disease, reduced LVEF (<35%), and at high risk for recurrent HF‐related events, despite optimal medical therapy, will be randomized 1:1 to receive 600 × 10 6 bone marrow‐derived and lineage‐directed autologous cardiopoietic stem cells administered via a retention‐enhanced intramyocardial injection catheter or a sham procedure. The primary efficacy endpoint is a hierarchical composite of mortality, worsening HF, Minnesota Living with Heart Failure Questionnaire score, 6 min walk test, LV end‐systolic volume, and LVEF at 9 months. The secondary efficacy endpoint is the time to cardiovascular death or worsening HF at 12 months. Safety endpoints include mortality, readmissions, aborted sudden deaths, and serious adverse events at 12 and 24 months. Conclusion: The CHART‐1 clinical trial is powered to examine the therapeutic impact of lineage‐directed stem cells as a strategy to achieve cardiac regeneration in HF populations. On completion, CHART‐1 will offer a definitive evaluation of the efficacy and safety of cardiopoietic stem cells in the treatment of chronic ischaemic HF. Trial registration: NCT01768702